A monograph of Hydriastele (Areceae, Arecaceae) in New Guinea and Australia - Petoe, Peter; Heatubun, Charlie D.; Baker, William J. (Phytotaxa, 2018)
A taxonomic revision of the genus Hydriastele H.Wendl. & Drude in New Guinea, Australia and immediately adjacent islands is presented. We recognise 25 species from this area including three new species of robust tree palms from New Guinea: Hydriastele calcicola, H. lanata and H. wosimiensis. All species are described in full in the taxonomic treatment, with accompanying botanical illustrations, photographs, distribution maps and preliminary IUCN Red List Assessments. In addition, a key to the species in New Guinea and Australia is provided as well as a systematic conspectus placing all 39 accepted species of Hydriastele in an informal infrageneric framework.